The impact of income distribution on house prices - M. Utku Ozmen; M. Koray Kalafatcilar; Erdal Yilmaz (Central Bank Review (CBR), 2019)
Housing market developments have been attracting a great deal of attention in Turkey. Concerns related to supply, particularly at the higher segment of the market, lead these discussions. In this respect, basic regression estimations indicate that over the post-2010 period, income elasticity of house price changes is negative, despite housing being a normal good. In order to reveal the underlying reason, we discuss the role of income distribution. Our empirical analyses suggest that the share of bottom (the top) income quintiles are positively (is negatively) correlated with house price changes. Given the current ample stock of houses, at the high-end of the market, a demand surge led by an increase in the income share of the top income quintile may not put pressure on house prices. In addition, the declining income share of bottom three income quintiles may lead to a reduction in their housing demand. Thus, policies directed to improving income equality might help mitigate the imbalances in the housing market.
Keywords: 330; Housing market; Income distribution; Turkey